Financial constraints and firm post-entry performance - Brito, Paulo (1994)
Firms finance production by internally generated funds and external loans. The benefits of leverage, however, come with a cost. This cost is related to the asymmetry of information banks have concerning the uncertainty of the output price of firms, which can imply bankruptcy and the uncertainty about the quality of the firm. As time evolves banks learn about the firm and adjust the terms of the loan contract. Because of this, firms do not have equal access to credit: small, young firms face greater binding debt constraints than more mature firms with well known prospects. The firm survival rate, as well as the firm rate of growth, due to liquidity constraints, are, therefore, important issues in analyzing firm post-entry performance. Our model provides a new approach to the study of firm demography based on the interaction between financial and production decisions..